Assessing Continuing Medical Education Needs in New Mexico - Kantrowitz, Martin P. (1983)
In 1981 a decision was made by the University of New Mexico School of Medicine to create a new Office of Community Professional Education whose primary function was to create continuing medical education programs tailored to its constituency. To accomplish this, a needs assessment survey was distributed to a stratified random sample of members of the New Mexico Medical Society practicing throughout the state to determine preferred learning styles, locations of programs and times of year, as well as other determinants for attending such programs. The survey was received by 647 physicians and 469 returned them—a response rate of 72.4 percent. Conclusions reached as a result of the needs assessment will serve as a basis of policy formation for the delivery of continuing medical education at the University of New Mexico School of Medicine.